(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: The third trimester represents a critical window in pregnancy when these hematologic changes could have the greatest impact. Therefore, understanding how coronavirus disease 2019 (COVID-19) infection influences blood profiles during this period is vital for clinical management and risk stratification. In Kenya, while national guidelines recommend laboratory evaluation, including complete blood count, c-reactive protein (CRP), lactate dehydrogenase (LDH), and coagulation profiles for pregnant women with suspected or confirmed COVID-19, there is a paucity of local data documenting these hematologic trends. Objective: To investigate hematologic profile differences between pregnant women in the third trimester with and without COVID-19 infection. Methods: A cross-sectional comparative study was employed to compare hematological parameters in pregnant women with and without COVID-19 between May 1st and August 31st, 2021. We recruited 60 eligible patients from the Nairobi hospital using purposive sampling. We assessed the complete blood count, coagulation profile, lactate dehydrogenase, and C-reactive protein. Results: Pregnant women with COVID-19 had significantly higher levels of neutrophils, prothrombin time, CRP, and LDH compared to those without, with respective AORs of 9.50 (p<0.01), 11.52 (p=0.001), and 3.06 (p=0.078). No significant differences were observed in white blood cells, basophils, and international normalized ratio after adjusting for age, parity, COVID-19 vaccination, and fetus number. Conclusion: This study reported significant associations between neutrophil count, prothrombin time, CRP, LDH levels, and COVID-19 infection status in pregnant women. These indices may aid in distinguishing healthy pregnant women from those with COVID-19 infection. Keywords: COVID-19 infection, pregnant women, third trimester, blood profile